2019
DOI: 10.1021/acs.organomet.9b00454
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Rhodium Porphyrin Complexes with Primary Alcohols under Basic Conditions

Abstract: Primary alcohols were successfully utilized as the alkylating reagents to conveniently access rhodium porphyrin alkyl complexes in up to 91% yields under basic conditions. Mechanistic investigations suggest two possible pathways for the C–O bond cleavage: (1) nucleophilic substitution with rhodium­(I) porphyrin anion and (2) a borrowing hydrogen pathway via rhodium­(III) porphyrin hydride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Previously, we reported that Rh­(ttp)­Cl could cleave the C–OH bond of benzyl alcohols and aliphatic alcohols in benzonitrile solvent under basic conditions at 120 °C to form Rh­(ttp)­Bn and Rh­(ttp)-alkyls, respectively . Considering the analogous reactivity of Ir­(por) complexes to Rh­(por) complexes in bond activation, we anticipated that the C–O bonds of various alcohols could be cleaved with Ir­(ttp)­(CO)Cl ( 1a ) under the above conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we reported that Rh­(ttp)­Cl could cleave the C–OH bond of benzyl alcohols and aliphatic alcohols in benzonitrile solvent under basic conditions at 120 °C to form Rh­(ttp)­Bn and Rh­(ttp)-alkyls, respectively . Considering the analogous reactivity of Ir­(por) complexes to Rh­(por) complexes in bond activation, we anticipated that the C–O bonds of various alcohols could be cleaved with Ir­(ttp)­(CO)Cl ( 1a ) under the above conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, Ir­(ttp)­OCH 2 Ph can be generated by the reaction between PhCH 2 OH ( 2a ) and Ir­(ttp)­OH from the ligand substitution of Ir­(ttp)­(CO)Cl ( 1a ) and KOH. Ir­(ttp)­OCH 2 Ph then undergoes β-H elimination with KOH to yield the Ir­(ttp) − anion and benzaldehyde. , Ir­(ttp) − can also be protonated to Ir­(ttp)H ( 1b ) by H 2 O (the p K a of Ir­(ttp)H is 15). , Subsequently, the nucleophilic Ir­(ttp) − anion attacks the carbonyl carbon in benzaldehyde to give the α-hydroxyalkyl complex Ir­(ttp)­CH­(OH)­Ph upon protonation with H 2 O. , Finally, Ir­(ttp)­CH­(OH)­Ph can be reduced by Ir­(ttp)H ( 1b ) to the desired C–O cleavage product Ir­(ttp)­CH 2 Ph ( 3a ) and Ir­(ttp)­OH, probably via σ-bond metathesis . Then, Ir­(ttp)­OH is either reused to react with PhCH 2 OH ( 2a ) or converted directly to the Ir­(ttp) − anion according to the pathway in Scheme .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 The Banerjee group added the nickel complex in this series in 2017. 22 Direct N-alkylation of amines with primary alcohols through the hydrogen auto-transfer reaction has been explored with rhodium-, [23][24][25] iridium-, [26][27][28][29] ruthenium-, [30][31][32][33] and osmium 34 -containing catalysts. Due to the ecological and economic benefits, it is desirable to use cheap metal-based catalysts in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%